TACTILE MAPS BASED ON 3D PRINTING TECHNOLOGY - Voženílek, Vít; Vondráková, Alena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The authors present the research seeking evaluating and developing aspects of interpretation and perception of geospace by modern tactile maps based on 3D printing. There are three newly introduced types of tactile maps. Map of type A is a tactile map printed by 3D printing technology as traditional relief tactile map with 5 mm thick background using both positive and negative relief with labelling by Braille letters. Map of type B is an inverse form of tactile map printed by 3D printing technology which will be used for casting type A tactile maps. Finally map of type C is a sound tactile map derived from map of type A posed onto box with digital voice records of geoinformation (attributes, navigations etc.) activated by touch on maps surface. The paper also describes present situation in tactile maps production and steps in recent testing the new type maps.